(untitled) (Mustansiria Dental Journal, 2018)
Cross-bite is one of important numerical anomalies of teeth . So that many studies have been carried out in different parts of world to find the prevalence of cross-bite. This study was conducted to assess cross-bite in a sample of Iraqi student. Which is essential for planning dental health services? The examination was carried out on 2210 subjects 1080 male and 1130 female, the age rang was (13-17 years) . The assessment procedures of cross-bit were carried out via intra-oral examination. The analysis of results showed that - The total percentage of cross-bite was recorded 18.8% . - The posterior cross-bite 10.4% while anterior cross-bite 8.5% . - The percentage of cross-bite in female 20.9% while in male 16.6% . - The percentage of unilateral cross-bite 7.3% while bilateral cross-bite 3% .